(ζ, δ(µ))-closed sets in strong generalized topological spaces. Issue 1 (1st January 2018) - Boonpok, Chawalit
Abstract: This paper deals with the concepts of ζ δ ( μ ) -sets and ( ζ, δ ( μ ) ) -closed sets in a strong generalized topological space and investigate properties of several low separation axioms of strong generalized topologies constructed by the families of these sets. Some properties of ( ζ, δ ( μ ) ) - R 0 and ( ζ, δ ( μ ) ) - R 1 strong generalized topological spaces will be given. Finally, several characterizations of weakly ( ζ, δ ( μ ) ) -continuous functions are discussed.